Pengembangan Ensiklopedia Keanekaragaman Hewan Vertebrata dan Invertebrata di Danau Lau Kawar Sebagai Sumber Belajar Untuk Meningkatkan Kemampuan Literasi Sains Mahasiswa - Monica Sitanggang; Masdiana Sinambela; Widya Arwita (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
The purpose of this study was to produce an encyclopedia of vertebrate and invertebrate animal diversity in Lake Lau Kawar that is valid, feasible, and effective as a biology learning resource based on scientific literacy. The low scientific literacy of students and the limited contextual biology learning resources based on local potential are problems in learning. This study used the ADDIE development model method which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of the study were students of the Biology Education Study Program in the Basic Ecology course. From the results of the research data processing, the results of the ADDIE development procedure were obtained, the validity of the material expert product was an average of 90.15% (very good), the validity of the design expert product was an average of 95.44% (very good), the validity of the learning expert product was an average of 88.86 (very good), the average lecturer response was 89.68% (very good), and the results of the N-Gain analysis of the results showed that the average value of the experimental class was higher than the control class. The results showed that the developed encyclopedia was in the very feasible category based on expert assessments and received very positive responses from users. Effectiveness testing showed an increase in students' scientific literacy skills, ranging from moderate to high. Therefore, this locally-based encyclopedia of animal diversity is suitable and effective as a biology learning resource in higher education.